Methodology for Determining the Speed‑Power Capabilities of Basketball Players - Viktor Koryahin; Halyna Hrebinka; Volodymyr Prystynskyi; Tetyana Prystynska (OVS LLC, 2022)
The study objective is to develop a methodology for determining the jump height and jumping endurance in basketball players of various gaming functions using modern nanotechnology and microprocessor systems, in particular smartphones, personal computers, etc. Materials and methods. The study used a method for determining jump height and jumping endurance using capacitive sensor devices based on a combination of modern nanotechnology and microprocessor systems, in particular smartphones, personal computers. Results. The study showed that the use of modern nanotechnology to monitor the jump height and jumping endurance allows you to study these indicators with high accuracy, which is very important in scientific research. The study showed that the absolute height of the jump in center players is 328.1 ± 7.88 cm, in attackers - 324.1 ± 6.62 cm, in defenders - 314.4 ± 8.65 cm. The relative height of the jump in defenders is 57.7 ± 6.86 cm, which is on average 8.2 cm more than in center players, and 5.3 cm more than in attackers (p < 0.001 and p < 0.02, respectively). Conclusions. The use of modern nanotechnology and microprocessor systems to determine the parameters of jump height and jumping endurance allows you to determine these parameters with high accuracy. The use of modern, accurate nanotechnology measurement and calculation of jump height and jumping endurance indicators using graphic data analysis provided a complete description and degree of development of various "jumping" qualities of basketball players. Studies have shown that the jump height and jumping endurance in basketball players of different roles (defenders, attackers, and center) differ with a high degree of reliability.